Viabilidade do consórcio de beterraba e caupi-hortaliça sob adubação com flor-de-seda e arranjos espaciais - Moraes, Edilson Carvalho de (2016)
The present work was conducted from August to November of 2014 at the 'Rafael Fernandes' Experimental Farm of the Federal Rural Semi-Arid University (FRSAU), with the objective of evaluating the viability of beet and vegetable-cowpea intercropping under fertilization with roostertree biomass and spatial arrangements of component cultures. The experimental design was a randomized complete block with four replications and the treatments arranged in a 4 x 3 factorial scheme, resulting from the combination of four quantities of roostertree biomass incorporated in the soil (20, 35, 50 and 65 t ha-1 on a dry basis) and three spatial arrangements between component cultures (2: 2, 3: 3 and 4: 4). The agronomic characteristics evaluated in the beet were: total, commercial and classified productivities of roots (extra, extra A, extra AA, great and scrap roots). In the vegetable-cowpea were evaluated: number of green pods per area, yield and dry weight of green pods, number of green grains per pod, weight of 100 green grains, and yield of green and dry grains. The agronomic and economic efficiency of the intercropping systems studied was evaluated through the indices of land equivalent ratio and productive efficiency, canonical variable score, gross and net returns, rate of return and net profit margin. There was no significant interaction between amounts of roostertree biomass incorporated into the soil and spatial arrangements for any characteristic evaluated in the beet, cowpea and the indices. The highest agronomic efficiency was obtained in the amount of 65 t ha-1 of roostertree biomass, while the highest economic efficiency was obtained in the amount of 28 t ha-1 of this manure. In absolute terms, the 2: 2 spatial arrangement provided the highest agroeconomic efficiency of the intercropped systems